Costs and underuse of insulin and diabetes supplies: Findings from the 2020 T1International cross-sectional web-based survey. (September 2021) - Pfiester, Elizabeth; Braune, Katarina; Thieffry, Axel; Ballhausen, Hanne; Gajewska, Katarzyna Anna; O'Donnell, Shane
Highlights: This study is the most extensive patient-led out-of-pocket cost survey for people living with type 1 diabetes. Worldwide, one out of every four respondents reported having underused their insulin at least once within the last year due to high cost. Significant positive correlation was observed between out-of-pocket expenses and reported household income for respondents with partial healthcare coverage. 63.2% of participants reported disruption of insulin supplies and 25.3% reported an increase of insulin prices related to the COVID-19 pandemic. Abstract: Aims: To investigate self-reported out-of-pocket expenses (OoPE) associated with insulin and diabetes supplies for people living with type 1 diabetes (T1D) worldwide. Methods: A web-based, cross-sectional survey was conducted from August to December 2020. The analysis included comparisons between responses from countries with no, partial, and full healthcare coverage. Results: 1, 066 participants from 64 countries took part in the study. 25% of respondents reported having underused insulin at least once within the last year due to perceived cost. A significant correlation was observed between OoPEs and reported household income for respondents with partial healthcare coverage. 63.2% of participants reported disruption of insulin supplies and 25.3% reported an increase of prices related to the COVID-19 pandemic. Conclusions: This study confirms previous reports of 25% of people in the United States with T1D using less insulin and/or fewer supplies at least once in the last year due to cost, a trend associated with the extent of healthcare coverage. Similar trends were observed in some middle/low income countries. Moreover, patients reported an increase in insulin prices and disruption of supplies during the COVID-19 pandemic. This study highlights the importance of self-reported OoPEs and its association with underuse/rationing of insulin.